HUBUNGAN INFEKSI DENGUE SEKUNDER DENGAN DERAJAT KEPARAHAN INFEKSI DENGUE - Beni Wibowo (Jurnal Medika Hutama, 2020)
Dengue is the most common vector-borne disease worldwide with varying clinical manifestations and laboratory features. A person can become infected with secondary dengue by different serotypes which can have severe manifestations. The results of the study found a comparison of clinical manifestations, platelet counts, liver enzymes, albumin, viral titers, antibodies and cytokines between primary and secondary dengue infections. Severe cases can cause shock called dengue shock syndrome (DSS). These findings support the hypothesis that secondary dengue infection by different serotypes may increase the severity of the infection. This is thought to be related to the theory of Antibody Dependent Enhancement (ADE). There is no specific therapy in the treatment of dengue, but the principle is to maintaining fluid balance.